2021
DOI: 10.3390/nu13020433
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Avoiding Nutrition Mistakes in Metropolitan Adolescents Are Associated with Sex, Nutrition Knowledge, Physical Activity, and Family Environment

Abstract: A comprehensive approach to the identification of the relationship between behaviors limiting nutrition mistakes, nutrition knowledge, and physical activity in the context of the family environment has not yet been widely explored. We aim to identify patterns of avoiding nutrition mistakes in high school students from Warsaw, Poland, and to assess their associations with nutrition knowledge (NK), physical activity (PA), body mass index (BMI), demographic, and family environment characteristics. A cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
0
9
1
2
Order By: Relevance
“…The results of recent studies performed among adolescents in Poland confirm only some of our study's findings. Drywie ń et al reported that among Polish metropolitan adolescents, favorable nutrition patterns occurred more frequently among girls, among those with siblings, and among respondents with insufficient rather than sufficient nutrition knowledge [62]. In this study group, similarly to adolescents from southern Poland, mother's education and household size were not significant predictors of nutrition patterns.…”
Section: Discussioncontrasting
confidence: 45%
“…The results of recent studies performed among adolescents in Poland confirm only some of our study's findings. Drywie ń et al reported that among Polish metropolitan adolescents, favorable nutrition patterns occurred more frequently among girls, among those with siblings, and among respondents with insufficient rather than sufficient nutrition knowledge [62]. In this study group, similarly to adolescents from southern Poland, mother's education and household size were not significant predictors of nutrition patterns.…”
Section: Discussioncontrasting
confidence: 45%
“…Considering the development of eating habits, it is essential to pay attention to the behaviours of children and adolescents in relation to nutrition to avoid developing and repeating inappropriate patterns in adulthood. In one of the papers presented [ 1 ], adolescents’ behavioural eating patterns were identified as “Prudent Ones” when they had knowledge about healthy eating and followed the recommendation, “Inconsequent” when follow recommendation partially, and “Rebels” when adolescents follow an unhealthy diet and eating behaviours. In this work, it was found that those more likely to follow healthy eating patterns and behaviours were students of female sex, with no siblings, better nutrition knowledge, and greater physical activity in leisure time.…”
mentioning
confidence: 99%
“…The adherence to the “Rebels” was observed in those of male sex, students with families larger than four people, whose mothers were in primary education and who had insufficient nutrition knowledge. However, none of the patterns were associated with BMI [ 1 ].…”
mentioning
confidence: 99%
“…А факторами, способствующими здоровому питанию, были знания и образование в области питания, планирование питания, участие в приготовлении пищи и физическая активность. Пищевое поведение родителей и социальное давление друзей оказывают как положительное, так и отрицательное влияние на индивидуальные пищевые привычки студентов американских колледжей [10].…”
unclassified
“…Среди факторов, влияющих на формирование привычек питания у молодёжи, называются уровень образования матери, размер семьи, включая наличие братьев и сестёр, гендерный аспект. Более рациональное питание отмечается у подростков-девочек и у учащихся с младшими братьями и сестрами, при этом у детей матерей с начальным образованием, у учащихся с недостаточными познаниями в области питания и у проживающих в семье из более чем 4 человек часто отмечаются признаки нездорового пищевого поведения [10].…”
unclassified